Early childhood care and education in Jamaica. Stakeholders' perceptions of global influences on a local space. Issue 10 (3rd October 2017) - Kinkead-Clark, Zoyah
ABSTRACT: This qualitative study aims to contribute to the dearth of literature pertaining to the impact of globalisation on education in Jamaica. Focussing on the early childhood level, it outlines the perceptions of stakeholders regarding the trajectory of sector development and highlights how they have had to accommodate their practices. Teachers, parents, principals and leaders in the early childhood field were interviewed. Two questions guided the research: (1) What are stakeholders' perceptions about external factors/entities influence on Jamaica's early childhood sector? (2) How have stakeholders' practices been influenced by these external factors/entities? Thematic analysis highlighted diverse perspectives from the participants. Some accepted the involvement on external agencies while others felt this was not in the best interest of the education sector. It is strongly recommended that countries, such as Jamaica, need to consider the support of external entities and the stipulations that come with this support, within a 'culturally relevant framework'.